Shocks to transition risk - Christoph Meinerding; Yves S. Schüler; Philipp Zhang (Deutsche Bundesbank, 2023)
We propose and implement a method to identify shocks to transition risk, addressing key challenges regarding its definition and measurement. Our shocks are instances where significant new information about the economic relevance of climate change increases the valuation of green firms over brown firms. To illustrate our method, we identify shocks to transition risk in the United States. These shocks have important aggregate effects, also inducing financial instability. They are associated with events that increase the likelihood of an orderly transition, and they specifically affect parts of the economy related to fossil fuels and energy. We show that these main results carry over to Germany and the United Kingdom. Still, we find an important role for country specificities.
Keywords: C30; E44; G12; Q43; Q54; Q58; 330; Transition risk; climate change; financial stability; portfolio sort; tex-tual analysis